The Effect of Using PjBL in Students’ Conceptual Understanding and Science Process Skills - Sukma Wahyu Wijayanti; Anti Kolonial Prodjosantoso; Febrian Solikhin (Jurnal Pendidikan dan Pembelajaran Kimia, 2021)
Abstract: The Effect of Using PjBL in Conceptual Understanding and Science Process Skills Students’. Objectives: This study is a quasi-experimental study that aims to understand whether there are differences in the ability to understand the concept and science process skills among learners using a PjBL model with learners using the 5M learning model on Acid-Base material of high school Class XI.  Methods: The research sample was taken by cluster random sampling technique and obtained class XI MIA 1 as the Experimental Class and class XI MIA 3 as the Control Class. Data were collected by the test method to measure the conceptual understanding and non-test methods to measure the science process skills. The analysis of hypothesis testing was carried out by using the manova test. Findings: The results showed that the Hotelling's Trace value on the manova test had a significance of 0.793. Conclusion: there is no difference in the ability to understand concepts and science process skills between students who use PjBL models and students who use 5M learning models.